1978
DOI: 10.1128/aem.35.3.467-470.1978
|View full text |Cite
|
Sign up to set email alerts
|

Adaptational change in proline and water content of Staphylococcus aureus after alteration of environmental salt concentration

Abstract: Adaptation of Staphylococcus aureus to a change in salinity was studied by estimating the intracellular content of water and proline after alteration of the salt concentration of the culture medium. The intracellular water content of S. aureus cultured in normal broth was 1.70 g/g (dry weight). After transfer to 1.8 M NaCl-containing broth, the water content decreased to 0.80 g/g (dry weight) within 1 min. After changing the salt concentration of the medium, intracellular free proline (assumed to be one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…The mechanism responsible for this regulation has not been studied. However, Staphylococcus alureius can accumulate high concentrations of proline in response to osmotic stress as a result of transport but not by increased synthesis (4,125). In general, gram-negative bacteria achieve high intracellular concentrations of proline during osmotic stress only by enhanced transport.…”
Section: Osmoprotectantsmentioning
confidence: 98%
“…The mechanism responsible for this regulation has not been studied. However, Staphylococcus alureius can accumulate high concentrations of proline in response to osmotic stress as a result of transport but not by increased synthesis (4,125). In general, gram-negative bacteria achieve high intracellular concentrations of proline during osmotic stress only by enhanced transport.…”
Section: Osmoprotectantsmentioning
confidence: 98%
“…Therefore, the observed stability of the healthy human skin microbiome following DSC reflects only total community membership, and does not take into account molecular and biochemical capabilities. In addition, several culturebased studies have indicated that skin commensals are halotolerant, and therefore the microbial community may not be affected dramatically by exposure to the high salinity of the Dead Sea (30,31).…”
Section: Advances In Dermatology and Venereologymentioning
confidence: 99%
“…In bacteria, until then, only amino acids like proline and glutamic acid had been suspected of serving an osmotic function. However, the few reports available were not only inconclusive, contradicting each other as to the presence of an ionic cytoplasma, but had also failed to distinguish between de novo synthesis and uptake of solutes from the growth medium [43][44][45][46]. In addition, due to analytical problems, the most common compatible solutes remained undetected and the apparent failure to meet osmotic balance led to the proposal of a hypoosmotic cytoplasm [47,48].…”
Section: The Spectrum Of Compatible Solutesmentioning
confidence: 99%